Alopecic and aseptic nodules of the scalp with trichoscopic and ultrasonographic findings - Anna Isabel Lazaro-Simo; Maribel Iglesias Sancho; Monica Quintana-Codina; Elena Del Alcázar Viladomiu; Pau Umbert Millet; Montse Salleras Redonnet (Wolters Kluwer Medknow Publications, 2017)
Alopecic and aseptic nodules of the scalp (AANS) is a rare entity, etiology of which is already unknown. It consists of a few dome-shaped, skin-colored nodules associated with nonscarring alopecia. They are usually located in the upper part of the occiput and surrounded by normal scalp. Most of the times, a biopsy is performed to make an accurate diagnosis. AANS have a good prognosis and even can resolve spontaneously. We present a new case of this entity with the description of trichoscopic and ultrasonographic findings that have recently been reported. These noninvasive techniques are useful for the diagnosis and could replace histological examination in the near future.